Investigating the therapeutic benefits of companion animals: Problems and challenges - Franklin, Adrian; Emmison, Michael; Haraway, Donna; Travers, Max (Qualitative Sociology Review, 2007)
To investigate the health benefits of companion animals in a way that goes beyond finding statistical patterns involves appreciating the philosophical debates about the nature of animal consciousness that engage an inter-disciplinary field of scholarship cutting across the Great Divide of the hard sciences and humanities. It also requires developing a methodology to conduct empirical research which is often viewed as of secondary importance by researchers wishing to make a philosophical case about human beings and modernity. This paper considers the achievements of qualitative sociologists, particularly in the field of post-Meadian symbolic interactionism who have addressed these issues, and discusses ways of extending and deepening this agenda through crossfertilization with similar work in ethnomethodology, conversation analysis and post-humanist sociology in investigating the health benefits of dogs.